Perbandingan Kadar C-Reactive Protein Terhadap Fase Pemberian Obat Anti Tuberkulosis - Amalia Ovi Mustika Seno; Dita Pratiwi Kusuma Wardani; Supriyadi Supriyadi; Arif Mulyanto (Universitas Muhammadiyah Surabaya, 2022)
Pulmonary tuberculosis is a disease caused by Mycobacterium tuberculosis. C-Reactive Protein (CRP) is produced in the body by the liver in response to inflammation caused by Mycobacterium tuberculosis infection. CRP as the main mediator of the non-specific immune system, and the concentration will increase to 1000 times higher than normal value in the event of tissue injury or infection. The aim of this study was to determine the comparison of CRP levels to the phase of anti-tuberculosis drug administration in pulmonary tuberculosis patients. The study was conducted by cross sectional study with a semi-quantitative method in June - July 2020 in Purwokerto Community Lung Health Center. The number of samples as much as 24 TB patients which is 12 TB patients in 0 month and 12 TB patients in 6 months. Data were analyzed by Mann Whitney Test. The mean rank in 0 month was 18.08 with median (min-max) 12 (12-24) mg / dL, whereas mean rank for 6 months was 6.92 with median (mix-max) was 0 (0- 12) mg / dL. Serum CRP levels in pulmonary TB patients in the 0-month treatment phase are higher than CRP levels in the 6-month treatment phase (p = 0,000).